Redox-assisted multicomponent deposition of ultrathin amorphous metal oxides on arbitrary substrates: highly durable cobalt manganese oxyhydroxide for efficient oxygen evolution. Issue 37 (5th September 2018) - Jhang, Ren-Huai; Yang, Chang-Ying; Shih, Ming-Chi; Ho, Jing-Qian; Tsai, Ya-Ting; Chen, Chun-Hu
Abstract : Large-scale amorphous metal oxide films deposited on arbitrary substrates via redox interaction exhibit greater efficiency and durability in electrocatalytic oxygen evolution than benchmark materials. Abstract : Deposition of ultrathin multicomponent coatings (<10 nm) commonly encounters difficulties of discontinuous grains, elemental segregation, and specific limits of dimensions and physical properties of substrates. We present a large-scale, solution-processable deposition of metal oxides capable of introducing diverse elemental combinations (ternary oxides of Fe, Mn, Co) and conducting substrate-universal deposition (including non-conductive plastics) under aqueous conditions. The redox-coupled film growth of amorphous binary cobalt manganese oxyhydroxide (CMOH) results in homogeneous elemental distribution, strong film adhesion and integrity, lower sheet resistance (7.41 to 13.0 × 10 7 Ω sq −1 ), and high visible light transparency (98.4%). The effects of deposition time, temperature, precursors, additives, and elemental ratios on film growth and compositions were investigated through cross-section, in situ growth monitoring, and elemental analysis. Experimental studies and molecular dynamics (MD) simulations reveal the strong dependence of film thickness on precursor anions, where acetate anions are responsible for achieving ultrathin deposition (6–10 nm). Amorphous CMOH shows higher OER activities (overpotential of 0.39 V) and more durable stability compared to its crystalline counterpart and benchmark RuO2 (overpotential of 0.59 V). Various electrodes (Ni foam, carbon cloth, Cu foil, and glassy carbon) exhibit significantly enhanced OER performance with CMOH coating.